PREPARATION, PHYSICAL CHARACTERIZATION, AND PHARMACOKINETIC STUDY OF DOCETAXEL NANOCRYSTALS - ARVIND GANNIMITTA,; PRATHIMA SRINIVAS,; VENKATESHWAR REDDY A,; PEDIREDDI SOBHITA RANI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of this study was to prepare and evaluate the nanocrystal formulation of docetaxel. Methods: Docetaxel nanocrystals were formulated to improve the water solubility. Docetaxel nanocrystals were prepared by nanoprecipitation method using Tween 80, egg lecithin, and povidone C-12 as stabilizers and poly(lactic-co-glycolic acid) (PLGA) as polymer in acceptable limits. A total of 16 formulations were prepared by changing stabilizer and polymer ratios. The prepared nanocrystals were characterized by particle size, zeta potential, crystalline structure, surface morphology, assay, saturation solubility, and in vitro drug release. Results: Based on particle size, polydispersity index, and zeta potential data, four formulations were optimized. The formulation containing Tween 80 as stabilizer has shown lowest particle size and better drug release than the formulations containing egg lecithin and povidone C-12 as stabilizers. The formulation containing Tween 80 and PLGA has shown still lower sized particles than the Tween 80 alone and exhibited prolonged sustained drug release. The release kinetics of formulations containing Tween 80 and PLGA followed zero-order release kinetics and formulations containing egg lecithin and povidone C-12 followed Higuchi diffusion (non-Fickian). Conclusion: From the study, we concluded that as the type and concentration of stabilizer changed the size and shape of the crystals were also changed and the formulations showed sustained drug release with non-Fickian diffusion.